E-Government Sebagai Upaya Dalam Meningkatkan Kualitas Pelayanan Publik Di Kabupaten Pamekasan - Anisa Kurniatul Azizah; Laili Dwi Agustina (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2023)
The purpose of this study is to analyze and study E-Government as an effort to improve the quality of public services in Pamekasan Regency. Pamekasan Regency applies the concept of E-Government in the form of an application, but is still experiencing difficulties in the development planning process. This research is a qualitative research with research subjects namely Pamekasan Regency. The research method used is observation and documentation techniques. The results of the study show that the government has succeeded in innovating in the form of "Pamekasan Smart" with the aim of making it easier for the public to report various problems related to development in Pamekasan Regency, but there are still inhibiting factors such as Skill Gaps. In order to overcome this, the government made several efforts such as signing an MoU with UPT BPSDMP Kominfo Surabaya. Thus, the government must be able to utilize human resources who are competent in Smart Government according to their respective fields so that later they can optimally manage the implementation of E-Government in public services.